Design of blockchain supported security function for IoT - Tan, Jervin Guan Yu (Nanyang Technological University, 2021)
The usage of Internet of Things devices has increased significantly in the past few years, due to their ability to greatly improve upon the quality of service across many industries. However, the introduction of Internet of Things devices creates associated security concerns. By design, such devices are typically small and computationally lightweight to minimise costs for widespread deployment. Their lack of computational and storage abilities leaves them vulnerable to many security flaws as they lack the ability to use conventional security protocols to defend themselves. Blockchain, another technology that has been gaining wider use in recent years, may hold the potential to secure the Internet of Things due to its innate secure design. However, blockchain technology and the Internet of Things have conflicting properties that make integration attempts challenging. Chiefly, the secure nature of conventional blockchains is currently tied to the high computational requirements behind their operation, which Internet of Things devices are unable to support. In this paper, an in-depth introduction to both technologies is provided as a preface to the presented survey on the current research efforts into integrating the two technologies.